The Effect Of Capital Structure, Profitability, And Liquidity On Company Value In Consumer Goods Sector Companies Listed On The Indonesia Stock Exchang - Kartika Sari Dewi (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
This study aims to analyze the effect of capital structure, profitability, and liquidity on firm value in consumer goods companies listed on the Indonesia Stock Exchange. Firm value is an important indicator because it reflects market assessment of corporate performance and investor expectations. This research uses a quantitative approach with secondary data obtained from annual financial reports and stock market data. The population consists of consumer goods companies listed on the Indonesia Stock Exchange, while the sample is selected using purposive sampling based on data completeness during the observation period. The analytical method used is multiple linear regression with firm value proxied by Price to Book Value, capital structure proxied by Debt to Equity Ratio, profitability proxied by Return on Assets, and liquidity proxied by Current Ratio. The results indicate that capital structure and profitability have a positive and significant effect on firm value, while liquidity has a positive but insignificant effect. These findings imply that investors pay more attention to debt policy and profitability when assessing consumer goods companies.